ANALISIS KEMOMETRIKA KANDUNGAN FITOKIMIA DENGAN AKTIVITAS ANTIACNE EKSTRAK BUAH PARIJOTO (Medinilla speciosa Blume) - Ameliya, Ameliya; Endang Setyowati; Emma Jayanti Besan (Yayasan Nusantara Hasana Berdikari, 2025)
Parijoto fruit has a variety of phytochemical compounds, such as flavonoids and phenolics, that are known to have potential as antiacne agents. This study aims to analyze the relationship between total and total phenolic flavonoid content with the antiacne activity of 70% ethanol extract and ethyl acetate parijoto fruit through chemometric analysis. This study used UV-Vis spectrophotometry to measure total flavonoid and phenolic content, with antiacne activity measured using the disc method at 20%, 30%, and 40% extract concentrations. The results showed that 70% ethanol and ethyl acetate extracts had flavonoid levels of 2.443 ± 0.029 (mgEK/mL) and 0.829 ± 0.013 (mgEK/mL), respectively, while the total phenolics were 4.622 ± 0.004 (mgEAG/mL) and 1.734 ± 0.012 (mgEAG/mL). Tests of antiacne activity against Staphylococcus aureus at concentrations of 20%, 30%, and 40% showed that 70% ethanol extract had strong activity, with consecutive inhibition zones of 11.8 ± 0.29 mm; 13.8 ± 0.29 mm; and 16.8 ± 0.76 mm. Ethyl acetate extract showed moderate activity with an inhibition zone of 7.2 ± 0.29 mm; 8.3 ± 0.58 mm; and 8.8 ± 0.29 mm. Chemometric analysis showed a positive relationship between flavonoid and phenolic content with antiacne activity, both in 70% ethanol extract and ethyl acetate. Ethanol extract of 70% parijoto fruit has higher levels of total flavonoids, total phenolics, and antiacne activity than ethyl acetate.